A cognitive explanation of the perceived normativity of cultural conventions. (6th November 2019) - Slors, Marc
Abstract : I argue that cultural conventions such as social etiquette facilitate a specific (non‐Lewisian) kind of action coordination—role–interaction coordination—that is required for division of labour. Playing one's roles and coordinating them with those of others is a form of multitasking. Such multitasking is made possible on a large scale because we can offload cognition aimed at coordination onto a stable infrastructure of cultural conventions. Our natural tendency to prefer multitasking in instances where one task requires low cognitive control can thus explain our preference for and expectation of familiar cultural conventions—that is, their perceived normativity.